2014
DOI: 10.3390/e16073573
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Entropy Generation under Stall Conditions in a Centrifugal Fan

Abstract: Rotating stalls are generally the first instability met in turbomachinery, before surges. This 3D phenomenon is characterized by one or more stalled flow cells which rotate at a fraction of the impeller speed. The goal of the present work is to shed some light on the entropy generation in a centrifugal fan under rotating stall conditions. A numerical simulation of entropy generation is carried out with the ANSYS Fluent software which solves the Navier-Stokes equations and user defined function (UDF). The entro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…We previously performed an experimental study on rotating stall in a centrifugal fan. The simulation results and experimental results indicated stall frequencies of 14.15 Hz and 14.4 Hz, 7 respectively. Thus, the simulation results exhibited good agreement with the experimental results, and the correctness of the simulation results was verified.…”
Section: Grid Divisionmentioning
confidence: 88%
“…We previously performed an experimental study on rotating stall in a centrifugal fan. The simulation results and experimental results indicated stall frequencies of 14.15 Hz and 14.4 Hz, 7 respectively. Thus, the simulation results exhibited good agreement with the experimental results, and the correctness of the simulation results was verified.…”
Section: Grid Divisionmentioning
confidence: 88%
“…Zhang et al. 13 studied KED in a centrifugal fan under rotating stall conditions and showed that energy dissipation increases after stall inception. High energy dissipation moves along the circumferential and axial directions and combines into one stall cell.…”
Section: Introductionmentioning
confidence: 99%
“…Dalir (2014) studied the non-Newtonian fluids, such as Jeffrey's flow on the tensile plates, and used computational fluid dynamic methods to analyze the generation of entropy. Zhang et al (2014) simulate the entropy generation of centrifugal fans under stall conditions. Nouwrozi (2012) analyzed the combined flow in a vertical channel under constant flux and concluded that under optimal conditions, the contribution of thermal entropy generation is about four to five times the frictional entropy generation.…”
Section: Introductionmentioning
confidence: 99%